Physicians’ and Nurses’ Perceptions and Attitudes Toward Sickle Cell Disease - Malak Ahmed Alomran; Fatimah Naseer Alhassan; Mohammed Hussain Alhassan; Yassmin Abdrabalrasso Almanasf; Lulwah Eid Rashed Albakheet; Arafat Matoq Al Khalifa; Duaa Hussain Ali Alabdullah; Taha Saad Majeed Al Muway; Wejdan Mustafa Mohammed Aljuraydan; Hajer Ahmed Alhzoom; Ayat Abdullah Alghuwinem; Abdulmajeed Jassam Alhussain; et al. (International Journal of Scientific Research and Innovative Studies, 2022)
Sickle cell disease (SCD) is a complex genetic disorder that affects millions of people worldwide. This review aims to explore physicians' and nurses' perceptions and attitudes toward sickle cell disease, including their understanding of the disease, its management, and the challenges faced by patients living with SCD. By examining healthcare providers' perspectives, this review seeks to identify areas for improvement in the care and treatment of individuals with SCD.